Legal and Institutional Analysis of the Structural and Functional Position of Infection Prevention and Control Nurses - Ni Luh Putri Suwandewi; I Nyoman Bayu Mahendra (PROMOTOR, 2026)
Infection Prevention and Control Nurses (IPCNs) play a strategic role in ensuring patient safety through the implementation of Infection Prevention and Control (IPC) programs in hospitals. In Indonesia, IPC implementation is regulated under Minister of Health Regulation Number 27 of 2017; however, the structural and functional position of IPCNs within hospital organizations remains insufficiently regulated. This study aims to analyze the normative framework of IPCNs and its implementation in hospital practice, as well as to examine the legal implications of existing regulatory gaps. The research employs a normative juridical approach combined with an empirical method through literature review of legal materials and semi-structured interviews with IPCNs in hospitals in Bali Province. Data were analyzed qualitatively by comparing normative provisions (das sollen) with empirical conditions (das sein). The findings indicate a significant gap between regulatory provisions and practical implementation, particularly in terms of organizational placement, authority, and competency standards of IPCNs. This inconsistency results in variations in IPC implementation across hospitals and may weaken legal certainty and patient safety outcomes. Furthermore, unclear regulatory positioning may increase hospital legal risks in cases of healthcare-associated infections. The study concludes that stronger regulatory integration is required to clarify the institutional role and authority of IPCNs in hospital governance.